Quality of life assessment in women after cervicosacropexy with polypropylene mesh for pelvic organ prolapse: a preliminary study - Majkusiak, Wojciech; Horosz, Edyta; Tomasik, Paweł; Zwierzchowska, Aneta; Wielgoś, Mirosław; Barcz, Ewa (Menopause Review/Przegląd Menopauzalny, 2015)
Aim of the study was to assess the changes in the subjective perception of quality of life in patients who underwent abdominal cervicosacropexy for pelvic organ prolapse. Material and methods: Forty patients with diagnosed pelvic organ prolapse (Pelvic Organ Prolapse – Quantification [POPQ] stage IV or IIIC) underwent abdominal supracervical hysterectomy and cervicosacropexy. The questionnaire concerning the quality of life was filled in before and 6 months after the surgery. Results: In all patients, an accurate prolapse correction was achieved. In 42% of patients, stress urinary incontinence (SUI) was diagnosed prior to surgery, while after the surgery in 38.24% (p > 0.05). In 50% of women, symptoms of overactive bladder (OAB) occurred pre-surgery. These symptoms were reported by 17.65% of patients postoperatively (p < 0.05). Urinary retention was observed in 32.36% before and in 2.5% after the surgery (p < 0.05). The average score of the quality of sexual life was 5.75 (SD 2.52, 95% CI: 4.41-7.1) before and increased to 7.93 (SD 1.77, 95% CI: 6.9-8.95) after the procedure (p < 0.05). The mean score of the overall quality of life in relation to POP before and after the procedure was 2.77 (SD 2.39, 95% CI: 1.87-8.64) and 9.03 (SD 1.08, 95% CI: 8.66-9.43), respectively (p < 0.001). Conclusions: These results show a highly significant improvement of the quality of life in patients who underwent abdominal cervicosacropexy for POP. The change in quality of their sexual life, reduced OAB and urinary retention rates, as well as improvement of the esthetic self-perception may have contributed to this positive effect.